Analysis of the Budget Management and Performance of the Health Center in the Covid-19 Era at the Nambo Health Center, Kendari City - Sri Mulyani; Muhammad Ikhsan Akbar; Azlimin Azlimin (Universitas Mandala Waluya, 2022)
As a public organization, the Primary Helath Center (PHC) financial management must be transparent, beginning with the budget implementation and planning phases. The purpose of this study was to ascertain how PHC financial performance was affected by financial management. Evaluation research is the kind of research that is used to help make decisions or give advice. The budget management and financial reports for the Nambo Health Center from 2019 to 2021 are the subject of the research and the object of the study. Regression analysis was used for data analysis. The study's findings on PHC budget management revealed an economic level of 92.46 %, an efficiency level of 131.90 %, and an effectiveness level of 118.90 %. The R2 test yielded 0.234 (23.4 %) while the Fisher's test yielded p = 0.075 (0.05). The study's conclusion is that the Nambo Health Center's financial management is efficient but not efficient. The variables of drug supplies, supplies of medical equipment and materials, supplies of dental tools and materials, and supplies of tools and materials, respectively, have a significant impact on the number of patients, accounting for 23.4% of the variable effect. The remaining influence is due to other factors that were not examined.